1987
DOI: 10.1104/pp.84.3.891
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Salicylhydroxamic Acid, BW755C, Eicosatetraynoic Acid, and Disulfiram of Hypersensitive Resistance Elicited by Arachidonic Acid or Poly-l-Lysine in Potato Tuber

Abstract: The hypothesis that arachidonic acid (AA) induction of sesquiterpene accumulation and browning in potato (Solanum tuberosum) is mediated by a lipoxygenase metabolite of AA was tested using lipoxygenase inhibitors. Salicylhydroxamic acid (SHAM) and 3-amino-1-(3-trifluoromethylphenyl)-2-pyrazoline hydrochloride (BW755C) delayed the response to AA. Inhibition by eicosatetraynoic acid (ETYA) and decreased steroid glycoalkaloid synthesis are observed. These changes are ascribed roles in the defense of potato agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…syringae pv phaseolicola (5), et al). Preisig and Kuc (19) suggested that LOX plays a role in the hypersensitive reaction of potato to Phytophthora infestans induced by arachidonic acid. The present study provides correlative evidence for an important role of LOX in plant disease resistance.…”
Section: Antifungal Activities Of Hydroperoxy and Hydroxy Fatty Acidsmentioning
confidence: 99%
“…syringae pv phaseolicola (5), et al). Preisig and Kuc (19) suggested that LOX plays a role in the hypersensitive reaction of potato to Phytophthora infestans induced by arachidonic acid. The present study provides correlative evidence for an important role of LOX in plant disease resistance.…”
Section: Antifungal Activities Of Hydroperoxy and Hydroxy Fatty Acidsmentioning
confidence: 99%
“…Firstly, arachidonic acid induces phytoalexin biosynthesis (Bloch et al, 1984) and hypersensitive cell death (Davis and Currier, 1988) in potato tubers. It has been proposed that the elicitor activity of arachidonic acid occurs through the action of lipoxygenase on this exogenous PUFA (Preisig and Kuc, 1987). Indeed, lipid hydroperoxides and their secondary derivatives such as free radicals, can exert deleterious effects on membranes, leading to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have different LOX isoforms with different catalytic specificities, but the factors that regulate the expression of these isoforms are largely unknown (12,18,34). Various roles have been proposed for LOXs that include a role in plant growth and development, senescence, and defense against insects and pathogens (7,17,18,28,34), although definitive proof for any of these is lacking. The normal substrates for plant LOXs are linoleic and linolenic acids, and LOX products of these fatty acids are metabolized to compounds that may function as signal molecules.…”
mentioning
confidence: 99%